Isavuconazole therapeutic drug monitoring in critically ill ICU patients: A monocentric retrospective analysis. Issue 7 (31st May 2022) - Höhl, Rainer; Bertram, Ralph; Kinzig, Martina; Haarmeyer, Golo‐Sung; Baumgärtel, Matthias; Geise, Arnim; Muschner, Dorothea; Prosch, Doris; Reger, Mira; Naumann, Hans‐Theodor; Ficker, Joachim H.; Kubitz, Jens; et al.
Abstract: Background: The broad‐spectrum triazole isavuconazole is used for the treatment of invasive aspergillosis and mucormycosis. Data regarding human plasma concentrations in clinical routine of the drug are rare. Objectives: Plasma concentrations of isavuconazole were determined in critically ill ICU patients while considering different patients' characteristics. Methods: Retrospective analysis of isavuconazole plasma concentrations were obtained as part of routine therapeutic drug monitoring (TDM) of ICU patients with invasive aspergillosis or other fungal infections treated with isavuconazole. Plasma levels 0–4 h after last dosing were defined as peak levels (Cmax ), those 20–28 h after last dosing as trough levels (Cmin ). Results: Overall, 223 isavuconazole levels of 41 patients were analysed, divided into 141 peak levels and 82 trough levels. The overall median Cmax was 2.36 μg/ml (mean 2.43 μg/ml, range 0.41–7.79 μg/ml) and the overall median Cmin was 1.74 μg/ml (mean 1.77 μg/ml, range 0.24–4.96 μg/ml). In total, 31.7% of the Cmin values of the total cohort were below the plasma target concentrations of 1 μg/ml, defined as EUCAST antifungal clinical breakpoint for Aspergillus fumigatus . Both peak and trough plasma levels of isavuconazole were significantly lower among patients with a body mass index (BMI) ≥25. In addition, a significant correlation was observed between isavuconazole trough levels and sepsis‐related organ failure assessment (SOFA) score. Conclusions: This study shows that isavuconazole plasma concentrations vary in critical ill ICU patients. Significantly lower isavuconazole levels were associated with elevated BMI and higher SOFA score indicating a need of isavuconazole TDM in this specific patient population.